Hybrid parental training to foster play-based early childhood development: Experimental evidence from Mexico - Cecilia Berlanga Alessio Robles; Emma Näslund-Hadley; Enrique Fernández García; Juan Manuel Hernández-Agramonte (Inter-American Development Bank (IDB), 2023)
Play during early childhood is key to stimulating children's physical, social, emotional, and cognitive development. However, research on play-based learning is largely limited to high-income countries, and little is known about the use of hybrid interventions (which combine in-person and remote contact) to promote play-based learning at home. This study estimated the effects of a hybrid parental program to promote play-based learning in the state of Morelos, Mexico. We observed a positive impact on parental investment, with an increase of 0.13 standard deviations (SD) when compared to the control group. The treatment group performed the following play-based activities more often than the control group: reading books/looking at pictures (0.12 SD), singing songs (0.11 SD), and playing with toys (0.17 SD), all of which incentivize learning and the development of emotional and cognitive skills in children. The study also found a significant effect of 0.19 SD on the Developmental Milestones Checklist for children of caregivers with the lowest level of parental investment at the baseline. Our findings support the importance of parental training for increased quality and extent of caregiver investments in play activities, especially among children in households with the lowest levels of caregiver investment at the baseline.
Keywords: C93; I20; I24; 330; Play-based learning; Early childhood development; Parental engagement; Hybrid education; Low- and middle-income countries; COVID-19; randomized controlled trial